National Crime Surveys: National Sample, 1979-1987 (Revised Questionnaire) ([Verlag nicht ermittelbar], 1987)
The purpose of the National Crime Surveys is to provide data on the level of crime victimization in the United States and to collect data on the characteristics of crime incidents and victims. Information about each household and personal victimization was recorded. The data include type of crime, description of the offender, severity of crime, injuries or losses, and demographic characteristics of household members.